Penerapan Hukum Oleh Hakim Dalam Menjatuhkan Putusan Di Luar Dakwaan Jaksa Penuntut Umum Dilema Antara Keadilan Dan Kepastian Hukum; Analisis Putusan Mahkamah Agung Nomor 1940 k/pid.sus/2015 - Ulfiyah Hasan; Alfitra Alfitra (JOURNAL of LEGAL RESEARCH, 2019)
AbstractThis study examines issues related to judges' considerations in issuing decisions outside the indictment of the public prosecutor in narcotics crime cases in the Decision of the Supreme Court Number: 1940 K / Pid.Sus / 2015. In addition, this study also tries to discuss the assessment of the principles of legal objectives, namely legal certainty and justice to the actions of judges in the Supreme Court Decision Number 1940 K / Pid.Sus / 2015 in narcotics crime cases. This research is juridical research using a case approach. Data in this study were collected using document studies. The document that is the source of the data in this study is the Supreme Court Decision Number 1940 K / Pid.Sus / 2015. Then the document is processed using the content analysis method. The results showed that the judges' basic considerations in the Supreme Court Decision Number 1940 K/Pid.Sus/2015 were quite critical in dropping decisions beyond the prosecutor's indictment. This consideration provides an illustration for the judge to be able to innovate the law and dare to come out of legal formalism to achieve justice.Keywords: Judge's Decision, Indictment, Narcotics Crime